Exploratory Factor Analysis of Critical Drivers for New Product Development in the Context of Dynamic Nanostore - Ortega-Jimenez, Cesar H; Sorto-Bueso, José Rodolfo; Melgar Martínez, Narciso A (LACCEI, 2024)
This study investigates the factors that influence New Product Development (NPD) in the dynamic context of nanostores in Honduras. Through an exploratory factor analysis based on a survey of 143 nanostores, four key factors in NPD practices were identified: Employee Involvement, Environment, Team Recognition, and Customer and Supplier Involvement. These factors explain 55% of the total variance in product development practices. The main purpose of the paper is to understand the determinants of NPD in this specific environment, providing an enriched view of industry practices and challenges. The findings offer valuable practical implications for nanostore managers, who can use these insights to optimize their product development strategies. Theoretically, the study expands the understanding of NPD practices in unique retail environments and demonstrates the effectiveness of exploratory factor analysis in identifying key factors. In addition, the paper contributes to the discussion on retail innovation by providing a novel and meaningful perspective on new product development in Honduran nano-stores.